(untitled) (Nepal Journal of Environmental Science, 2014)
Owing to widespread road widening activities and the growing vehicular traffic, air quality of Kathmandu Valley has been a matter of grave concern. In this study, we monitored air quality inside public vehicles of Kathmandu Valley which would help assess the exposure of public transport users to air pollution. Problem of particulate pollution, especially PM10, was found severe inside the buses. Carbon monoxide and total volatile organic compounds were mostly within acceptable levels but benzene exceeded guidelines in few samples. Benzene, toluene, ethylbenzene and xylene (BTEX) were dominant among all detected volatile organic compounds. There was high degree of correlation among BTEX. Similarly, significant correlation was found between carbon monoxide and total volatile organic compounds. PM10 and PM2.5 were also significantly correlated suggesting common source of emission. Gaseous pollutants had significant negative correlation with traffic speed suggesting that traffic congestion (responsible for low traffic speed and high traffic density) is causing higher emission.